Serum vitamin D metabolites and intestinal calcium absorption efficiency in women(1)(2)(3) - Aloia, John F (American Society for Nutrition, 2010)
Background: Vitamin D sufficiency may be determined by the serum concentration of 25-hydroxyvitamin D [25(OH)D] that results in maximal intestinal calcium absorption efficiency. However, some investigators questioned whether 25(OH)D concentrations above the concentrations associated with rickets or osteomalacia influence calcium absorption. Objective: We determined whether calcium absorption efficiency is related to serum 25(OH)D or serum 1,25-dihydroxyvitamin D [1,25(OH)(2)D] concentrations. Design: We measured calcium absorption efficiency in 492 black and white healthy women (age range: 20–80 y) by the single-isotope method with (45)Ca. Serum 25(OH)D concentrations were measured by a radioreceptor assay. Other relevant measurements included concentrations of serum 1,25(OH)(2)D, serum parathyroid hormone, serum creatinine, and serum estradiol, calcium intake, and bone mineral density. Results: There was no relation between serum 25(OH)D concentrations and calcium absorption efficiency. In development of a multivariate model, the 4 major determinants of calcium absorption efficiency were menopausal status, calcium intake, and serum estradiol and serum 1,25(OH)(2)D concentrations. There was an interaction between serum 25(OH)D and 1,25(OH)(2)D concentrations on calcium absorption efficiency. The relation between calcium absorption and 1,25(OH)(2)D was positive, and this relation was stronger for lower concentrations of 25(OH)D than for higher concentrations of 25(OH)D. Conclusion: The relation of serum 25(OH)D to calcium absorption is not useful as an indicator of vitamin D sufficiency.